Reducing the cost of energy used for adaptation by using different exterior wall covering materials in Iraq - Mahmoud Fadhel Idan (Institute of Advanced Engineering and Science, 2022)
This paper aimed to study how to reduce the amounts of heat transfer from or to the internal space of the building by covering its external walls with many locally available materials, thus reducing the rate of consumption of electrical energy used in adaptation, which leads to reducing energy consumption costs. The researcher built a model room with dimensions (1 x 1 x 2) m on the third floor of a building in Baghdad (L = 33.2 N), the dimensions of its walls (1 x 2 m) east for the installation of the sample, and the other surfaces are insulated with 200 mm polystyrene sheets. Use a 0.5 ton air conditioner to provide the room thermal comfort. The researcher found that the metal sheet with a thickness of 10 mm and covered with an insulating layer of thermoplastics is considered the best among the materials used in construction, as it saves 57% of the electrical energy consumed in air conditioning. While the use of marble, porcelain, helen stone, and fiberglass slabs with a thickness of 10 mm, comes last because it saves less than 30% of electrical energy.